The Epigenomics of Embryonic Pathway Signaling in Colorectal Cancer - Curt Balch; Curt Balch; Curt Balch; Jayaram B. Ramapuram; Amit K. Tiwari (Frontiers Media S.A., 2017)
Colorectal cancer (CRC) is the second-leading cause of cancer death in developed countries. While early detection (e.g., colonoscopy) generally yields excellent outcomes, metastatic and drug-resistant disease is uniformly fatal, and non-compliance for screening remains over 25%. Familial CRCs (10% of total cases) primarily include mutations in the gene APC. Somatic disease is linked to several environmental several risk factors, including mutations in WNT, KRAS, and TGFβ. To reflect the genesis/progression of CRC, a series of five discrete stages, from normal colon mucosa to fully invasive carcinoma, each regulated by specific "gatekeeper" genes, remains well-accepted after 20 years. However, many CRC tumors do not possess those particular mutations, suggesting alternative mechanisms. More recently, embryo-like "cancer stem cells" have been proposed to undergo self-renewal and drive tumorigenesis (and possibly, metastasis), as governed by specific "epigenomic" alterations. Here, we review recent literature describing possible mechanisms that underlie these phenotypes, including cancer "stemness," believed by many to associate with the epithelial-to-mesenchymal transition (EMT). We further propose that the maintenance of undifferentiated phenotypes, by the activity of distinct transcription factors, facilitates chromatin remodeling and phenotypic plasticity. With that regard, we support recent assertions that EMT is not an "either/or" event, but rather a continuous spectrum of mesenchymal vs. epithelial phenotypes (in various degrees of aberrant differentiation/undifferentiation). Finally, we discuss possible methods of pharmacologically targeting such aberrant epigenomes, with regard to their possible relevance toward halting, or even reversing, colorectal cancer progression.